Assessing the relative importance of factors influencing travel happiness. (July 2019) - Chen, Shuyan; Fan, Yingling; Cao, Yang; Khattak, Aemal
Highlights: Of factors examined, rest status is the most important factor of travel happiness. Interacting with others during trip is the second important factor. Travel purpose and education background strongly predicts travel happiness. Abstract: Travel happiness represents positive user experiences of transportation services and has a significant impact on people's overall happiness. Increasingly, studies have identified factors associated with travel happiness, which help identify strategies to improve transportation user experiences and identify innovative solutions for improving public health. Using data from the 2013 American Time Use Survey, we combined optimal scale regression, factor analysis, and analytic hierarchy process to assess the relative importance of various trip and personal factors influencing happiness during trips. We found that the degree of rest and whether the trip maker interacted with others during a trip were the most important factors affecting happiness during the trip. Transportation planners in the U.S. are recommended to invest in rest areas and transit shelters, identify strategies that can prevent people from travelling while fatigued, and provide opportunities for transportation users to interact with others while ensuring safety.